Transcription factors SOHLH1 and SOHLH2 coordinate oocyte differentiation without affecting meiosis I - Shin, Yong-Hyun (J Clin Invest, 2017)
Following migration of primordial germ cells to the genital ridge, oogonia undergo several rounds of mitotic division and enter meiosis at approximately E13.5. Most oocytes arrest in the dictyate (diplotene) stage of meiosis circa E18.5. The genes necessary to drive oocyte differentiation in parallel with meiosis are unknown. Here, we have investigated whether expression of spermatogenesis and oogenesis bHLH transcription factor 1 (Sohlh1) and Sohlh2 coordinates oocyte differentiation within the embryonic ovary. We found that SOHLH2 protein was expressed in the mouse germline as early as E12.5 and preceded SOHLH1 protein expression, which occurred circa E15.5. SOHLH1 protein appearance at E15.5 correlated with SOHLH2 translocation from the cytoplasm into the nucleus and was dependent on SOHLH1 expression. NOBOX oogenesis homeobox (NOBOX) and LIM homeobox protein 8 (LHX8), two important regulators of postnatal oogenesis, were coexpressed with SOHLH1. Single deficiency of Sohlh1 or Sohlh2 disrupted the expression of LHX8 and NOBOX in the embryonic gonad without affecting meiosis. Sohlh1-KO infertility was rescued by conditional expression of the Sohlh1 transgene after the onset of meiosis. However, Sohlh1 or Sohlh2 transgene expression could not rescue Sohlh2-KO infertility due to a lack of Sohlh1 or Sohlh2 expression in rescued mice. Our results indicate that Sohlh1 and Sohlh2 are essential regulators of oocyte differentiation but do not affect meiosis I.